Binding of the 5'-untranslated region of coronavirus RNA to zinc finger CCHC-type and RNA-binding motif 1 enhances viral replication and transcription - Tan, Yong Wah (2013)
Coronaviruses RNA synthesis occurs in the cytoplasm and is regulated by host cell proteins. In a screen based on a yeast three-hybrid system using the 5'-untranslated region (5'-UTR) of SARS coronavirus (SARS-CoV) RNA as bait against a human cDNA library derived from HeLa cells, we found a positive candidate cellular protein, zinc finger CCHC-type and RNA-binding motif 1 (MADP1), to be able to interact with this region of the SARS-CoV genome. This interaction was subsequently confirmed in coronavirus infectious bronchitis virus (IBV). The specificity of the interaction between MADP1 and the 5'-UTR of IBV was investigated and confirmed by using an RNA pull-down assay. The RNA-binding domain was mapped to the N-terminal region of MADP1 and the protein binding sequence to stem–loop I of IBV 5'-UTR. MADP1 was found to be translocated to the cytoplasm and partially co-localized with the viral replicase/transcriptase complexes (RTCs) in IBV-infected cells, deviating from its usual nuclear localization in a normal cell using indirect immunofluorescence. Using small interfering RNA (siRNA) against MADP1, defective viral RNA synthesis was observed in the knockdown cells, therefore indicating the importance of the protein in coronaviral RNA synthesis.